Development of a Path Loss Model for Wave Propagation Into Selected Buildings at Universiti Putra Malaysia - Roslee, Mardeni (2005)
In this thesis, the development of path loss prediction model for wave propagation into buildings at Universiti Putra Malaysia is described. Field strength measurements due to three base stations were carried out in three different buildings in the Universiti Putra Malaysia campus. The measurement setup consisted of an ADVANTEST U3641 Spectrum Analyzer and an AHSISAS-5 19-4 log periodic antenna A computer program has been developed to calculate the path loss from the measured field strength which in turn was used for comparison with available path loss models. The results indicate poor agreement between the measured and existing predicted path loss models where even the widely accepted COST 231 model deviated as high as 9.46%. The discrepancy between the measured and predicted path loss was even greater for other models such as the Microcell model (17.69%) and outdoor-indoor model (24.71%). An improved version of COST 23 1 model and an empirical path loss models have been proposed in this work to replace the COST 231 model. The improved COST 231 model was found from an optimization procedure by fitting the original model to the measured data, whilst the empirical model was obtained from regression analysis. The accuracy of the Improved COST 231 and empirical models was tested on different buildings and found to agree with measured data within 6.31%, and 7.85%, respectively. The Agilent VEE software was used to develop and execute the integrated ITMAPL program for wave propagation into buildings. The ITMAPL program is a user friendly program to calculate and display the path loss of radio propagation paths. It is implemented in the run time format version and has three options which are COST 231 model (CST), improved COST 231 model (ICS) and ITMANE new empirical model.